Effectiveness of Breathing Exercise on Pulse Rate and Blood Pressure Among Hypertensive Patients: DOI: https://doi.org/10.46610/RRMETN.2022.v04i02.003 - Dixit, Anand (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Objectives: To assess pulse and blood pressure before teaching breathing exercise, To assess the effectiveness of breathing exercise on the pulse rate and blood pressure among hypertensive patients and to find out the association of the study findings with selected demographic variables. Hypotheses: H1: There will be significant effect of breathing exercise on pulse rate and blood pressure of hypertensive patients. H2: There will be significant association between pulse rate and blood pressure selected demographic variable. Assumptions: The study assumes that Breathing exercise may have some effect on pulse rate and blood pressure, breathing exercise relaxes mind and body, Patient medication may have some effect on the pulse rate and blood pressure. Conceptual Framework: The framework is brief explanation of the theory or those portions of theory that are to be tested in a quantitative study. It helps to organize the study and provides a context for the interpretation of study results, The conceptual framework adopted in this study is based on the General systems theory. It explains the various parts of a system have functional as well as structural relationship between each other Conclusion: With the above findings it is clear that the Breathing exercises were found to be significantly effective in improving the systolic blood pressure, diastolic blood pressure and pulse rate of hypertensive patients. Analysis of data showed that there was significant difference between experimental group value and control group value.